Comparisons of Four Diet Quality Indexes to Define Single Meal Healthfulness. - Bullock, Sally L.; Miller, Hilary M.; Ammerman, Alice S.; Viera, Anthony J. (Journal of the Academy of Nutrition & Dietetics, 2022)
Many dietary indexes exist to evaluate nutrition quality, but few specifically assess the quality of a single meal. Our aim was to compare 4 different diet quality indexes in their ability to assess the nutrition quality of single meals. This was a secondary analysis of data from the PACE (Effects of Physical Activity Calorie Expenditure) food labeling study (2015-2017). Data were collected in business cafeterias in North Carolina and included photos of lunch trays before consumption from an adult population and serving sizes of each food item. Additional nutrient analysis was conducted to compile macro- and micronutrient data for each food item, in addition to servings provided from each food group. The main outcome was individual meal nutrition quality. Data from the PACE study were used to calculate the scores of the following diet quality indexes: Healthy Eating Index 2015, Dietary Approaches to Stop Hypertension accordance score, Main Meal Quality Index, and Nutrient Rich Foods Index. To score the meals, algorithms were created in SAS software, version 9.4, to combine individual foods and beverages into meals and calculate scores according to the individual index components. The total scores for each of the indexes were compared using Spearman correlation coefficients. A total of 8,070 observations or "meals" from 379 participants were scored for this study. The scores for each observation varied by index. The Spearman correlation coefficients between the indexes for the total score for all observations ranged from 0.26 to 0.68. The correlation coefficients did not change equally among the indexes when observations were excluded based on predefined criteria for what constitutes a meal. There is wide variability in scores of the 4 diet quality indexes analyzed in this study. In addition, the indexes show weak to moderate correlation, indicating that the appropriateness of the index will depend greatly on the study questions and objectives.